Entrepreneurship as a Living Research: Curiosity, Experimentation, and Adaptation among Young Entrepreneurs in HIPMI Denpasar - LARASDIPUTRA, Gde Deny (Journal of Governance, Taxation and Auditing, 2025)
Entrepreneurship is often portrayed as a journey of opportunity and innovation, yet beneath every entrepreneurial act lies a deeper process of learning through inquiry. This study explores how young entrepreneurs in the Association of Young Indonesian Entrepreneurs, Denpasar Branch (HIPMI Denpasar, Bali), integrate research-oriented thinking into their business practices—how curiosity evolves into experimentation, and experimentation into adaptation. Using a qualitative descriptive approach, five entrepreneurs were interviewed to reveal how they observe, reflect, and refine their strategies in navigating uncertainty. The findings uncover four interrelated themes: (1) curiosity as the origin of opportunity discovery, (2) informal research as a practical decision-making process, (3) experimentation as a learning strategy, and (4) adaptation as the foundation of sustainability. Together, these themes illustrate that entrepreneurship functions as a living form of research, where every action becomes a test, every reflection becomes data, and every adaptation becomes insight. The study contributes theoretically by reframing curiosity as a form of strategic intelligence, embedding research within entrepreneurial practice, and positioning community learning as the epistemic infrastructure for resilience. Practically, it suggests that young entrepreneurs already act as researchers in their daily work, and that entrepreneurial education should cultivate reflective inquiry rather than formulaic planning. By linking curiosity, reflection, and adaptation, this study affirms that to be an entrepreneur is to be a lifelong researcher—one who learns not in laboratories, but in life itself.